Acute and short-term efficacy of sauna treatment on cardiovascular function: Ameta-analysis. (20th August 2020) - Li, Zhongyou; Jiang, Wentao; Chen, Yu; Wang, Guanshi; Yan, Fei; Zeng, Tao; Fan, Haidong
Abstract: Objective: The role of sauna bathing in cardiovascular function treatment has been increasingly explored, but insufficient attention has been paid to its efficacy. We performed a meta-analysis to provide more evidence for the efficacy of sauna treatment in cardiovascular nursing. Methods: Sixteen peer-reviewed journal articles were screened to summarize the efficacy of the sauna on cardiovascular function. Both acute (0–30 min after the sauna) and short-term (2–4 weeks following the sauna treatment) efficacies were investigated. Results: For pooled acute efficacy, body temperature and heart rate significantly ( p < 0.001) grew by 0.94°C and 17.86 beats/min, respectively; reductions of 5.55 mmHg ( p < 0.001) and 6.50 mmHg ( p < 0.001) were also observed in systolic blood pressure and diastole blood pressure, respectively. For combined short-term efficacy, left ventricular ejection fraction (LVEF), 6-min walk distance, and flow-mediated dilation ( p < 0.001) increased by 3.27%, 48.11 m, and 1.71%, respectively; greater amelioration in LVEF was observed in participants with lower LVEF. The proportion of patients with New York Heart Association class III and IV decreased by 10.9% and 12.2%, respectively. Systolic blood pressure, diastolic blood pressure, brain natriuretic peptide concentration, left ventricular end-diastolic dimension, cardiothoracic ratio, and left atrial dimension reduced by 5.26 mmHg ( p < 0.001), 4.14 mmHg ( p < 0.001), 116.66 pg/mL ( p < 0.001), 2.79 mm ( p < 0.001), 2.628% ( p < 0.05), and 1.88 mm ( p < 0.05), respectively, while the concentration of norepinephrine in the plasma remained unchanged. Conclusion: Sauna treatment was found to play a positive role in improving cardiovascular function and physical activity levels, especially in patients with low cardiovascular function. These findings reveal that thermal intervention may be a promising means for cardiovascular nursing.